2012
DOI: 10.1364/ol.37.003504
|View full text |Cite
|
Sign up to set email alerts
|

High-contrast 40  Gb/s operation of a 500 μm long silicon carrier-depletion slow wave modulator

Abstract: In this Letter, we demonstrate a highly efficient, compact, high-contrast and low-loss silicon slow wave modulator based on a traveling-wave Mach-Zehnder interferometer with two 500 μm long slow wave phase shifters. 40 Gb ∕ s operation with 6.6 dB extinction ratio at quadrature and with an on-chip insertion loss of only 6 dB is shown. These results confirm the benefits of slow light as a means to enhance the performance of silicon modulators based on the plasma dispersion effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The exact reading of the actual n g is made difficult by the adiabatically-tapered shape, and further investigation is expected on this aspect. An asymmetric MZI configuration using a 2-mm-long delay line would have allowed a better reading of the n g number [16]. New device test structures including delay lines up to 2-mm-long are under fabrication for addressing this issue.…”
Section: -D Hcg Slow-waves Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact reading of the actual n g is made difficult by the adiabatically-tapered shape, and further investigation is expected on this aspect. An asymmetric MZI configuration using a 2-mm-long delay line would have allowed a better reading of the n g number [16]. New device test structures including delay lines up to 2-mm-long are under fabrication for addressing this issue.…”
Section: -D Hcg Slow-waves Performancesmentioning
confidence: 99%
“…Previous works have shown that, by a better understanding of the mechanisms governing the slow-light phenomena in photonic crystal waveguides, optimized designs can achieve dispersion-free light slow-down over several nanometers bandwidths, thus widening the spectral window over which the slow-light propagation regime takes place and adding extended functionality to the device itself [11]- [13]. Moreover, slow-light waveguides has been used in the recent past to realize more compact and efficient horizontal p-n junction modulators into Mach-Zehnder interferometers (MZI) configuration on SOI [14] - [16].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, slow light can provide enhancement of light-matter interaction in a way similar to optical resonators, but retaining the large bandwidth of traveling wave devices. Example applications are the realization of all-optical buffers and memories [3], or the enhancement in sensitivity of interferometers, for example in Mach-Zehnder modulators [4,5] or for sensing purposes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Significant milestones have been achieved during recent years through the plasma dispersion effect although mostly for digital applications [8]- [20], but so far very little attention has been 0733-8724 © 2013 IEEE paid to analog applications. As mentioned above, high linearity is required for RF signal transmission.…”
mentioning
confidence: 99%